Intergenerational Dynamics and Sustainability in Community-Based Tourism: A Case Study of Koh Kret - Mingjing Qu (SAGE Open)
This study explores the intergenerational dynamics within Koh Kret’s community-based tourism sector, addressing the challenges faced by older business owners and the reluctance of younger generations to inherit family businesses. Despite comprehensive analysis into sustainable tourism and cultural conservation, there are notable deficiencies in understanding the relationship between these elements, especially within the context of family-operated businesses. Through conducting thorough interviews with 25 community members, including local community leaders, older business owner, younger generation, and visitors, this research utilizes grounded theory to examine these interactions and formulate approaches to enhance youth engagement. Key findings will provide detailed insights into the operational difficulties of older entrepreneurs, uncover the motivations behind the younger generation’s reluctance, and propose actionable solutions to promote sustainable tourism. This research aims to fill a critical gap in the literature by offering a holistic approach to intergenerational challenges in community-based tourism, ensuring both the sustainability and cultural integrity of Koh Kret as a tourist destination.